Social Inclusion through the Eyes of Students: A Qualitative Study in Ethnically and Socioeconomically Diverse Schools - Budacu, Dumitru N.; Budacu, Dorina Gh. (Innovare Journal of Education, 2025)
This study examines how students perceive and experience social inclusion in ethnically and socioeconomically diverse school settings. Using a qualitative methodology, it captures the perspectives of 12 students aged 12 to 15 from urban middle schools in Romania. Interviews, designed with open-ended prompts, served as the primary method for obtaining insights, which were then explored using a thematic lens. Four key themes emerged: a conditional sense of belonging, peer relationships characterized by both solidarity and subtle exclusion, the ambivalent role of teachers in promoting inclusion, and unequal access to extracurricular opportunities. The findings reveal that social inclusion is not merely an institutional objective but a lived, emotional, and relational experience shaped by everyday school interactions. The study emphasizes the importance of culturally responsive and equity-oriented educational practices, highlighting the value of incorporating students' voices in shaping inclusive school environments.